Ceramic oxygen barrier material with low heat conductivity coefficient of sintered ceramic body and preparation method of ceramic oxygen barrier material
Through the preparation of ceramic oxygen barrier after low sintering, the complex manufacturing process of medium voltage fire-resistant cables and insufficient flame retardant performance are solved, and the effect of simplifying the process, reducing costs and improving fire-retardant performance is achieved.
Patent Information
- Application Number
- CN202411321552.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
AI Technical Summary
The manufacturing process of medium-voltage fire-resistant cables is complex and costly. The existing ceramic oxygen insulation materials lack flame retardant performance at high temperatures, making it difficult to meet the needs of higher safety standards in the future.
The ceramic oxygen barrier material after low sintering is used. The raw material components include EPDM resin, POE resin, vinyl silicone rubber, POE compatibility agent, MCA flame retardant, sericite powder, calcium silicate nanowhisker , ceramic additives, etc., through refining and double-step extrusion mechanisms, ceramic materials with good flame retardant properties and low thermal conductivity are formed.
The manufacturing process of medium voltage fire-resistant cables is simplified, the production cost is reduced, and the fire resistance of the cable and the three-point bending strength of the sintered ceramic body are improved, ensuring higher safety.
Smart Images

Figure BDA0005054093950000041 
Figure BDA0005054093950000051 
Figure BDA0005054093950000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a ceramic oxygen-insulating material with a low thermal conductivity of a sintered ceramic body and a preparation method thereof. Background Art
[0002] In modern power systems, medium-voltage power cables play a vital role. They not only connect various power facilities, but also ensure the stability and reliability of power transmission. However, in actual applications, cable fire accidents may occur due to various internal and external factors, such as overload and short circuit. Once such accidents occur, they will not only have a serious impact on the normal operation of the power system, but may also bring huge economic losses and safety hazards. Therefore, improving the fire resistance of cables is one of the key measures to ensure the safety of the power system.
[0003] For medium voltage fire-resistant cables, the fire resistance requirements are more stringent than those of traditional low voltage fire-resistant cables. In order to meet these requirements, the design of medium voltage fire-resistant cables usually does not adopt the traditional method of conductor wrapped with mica tape, because this design may not fully meet the electrical performance requirements of medium voltage cables. Instead, they often use ceramic polymer composite materials as fire-resistant layers, which can form a ceramic-like protective layer at high temperatures, thereby effectively preventing the spread of flames and protecting the inside of the cable from damage.
[0004] In addition, in order to further improve the fire resistance of the cable, a highly flame-retardant oxygen-insulating layer is usually added on the basis of the fire-resistant layer as a heat-absorbing layer. The main function of this layer is to absorb a large amount of heat at the beginning of the fire and inhibit the development of the flame by isolating oxygen. However, although such a double-layer design improves the safety of the cable, it also increases the complexity of cable manufacturing, resulting in a longer production cycle and an increase in material costs.
[0005] In view of the above situation, the development of a ceramic oxygen-insulating material with a low thermal conductivity of the sintered ceramic body and its preparation method will help simplify the manufacturing process of medium-voltage fire-resistant cables, reduce production costs, and ensure or even improve the fire resistance of cables. This is not only an advancement in cable manufacturing technology, but also a requirement to meet higher safety standards in the future. Summary of the invention
[0006] The object of the present invention is to provide a ceramic oxygen barrier material with low thermal conductivity of a sintered ceramic body and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.
[0007] The technical scheme for achieving the purpose of the present invention is: a ceramic oxygen barrier material with a low thermal conductivity of a sintered ceramic body, wherein the raw material components include, by weight: a base resin: 7 to 10 parts of EPDM resin, 11 to 10 parts of POE resin, and 4 to 6 parts of vinyl silicone rubber; 6 parts of POE compatibilizer, 25 to 30 parts of compound flame retardant, 25 parts of sericite powder, 5 parts of calcium silicate nano whiskers, and 10 to 12 parts of a ceramic additive; 0.5 to 0.8 parts of a silane coupling agent A-171, 0.12 to 0.2 parts of a vulcanizing agent, and a lubricant: 1 part of silicone powder and 0.4 to 0.8 parts of vinyl silicone oil.
[0008] Furthermore, the POE compatibilizer is at least one of POE-g-MAH and POE-g-GMA.
[0009] Furthermore, the compound flame retardant includes MCA flame retardant.
[0010] Furthermore, the compound flame retardant also includes diethyl aluminum hypophosphite coated phenyl silicone resin.
[0011] Furthermore, the porcelainizing aid is magnesium silicate coated with phosphate-based low-temperature glass powder.
[0012] Furthermore, the vulcanizing agent includes dicumyl peroxide.
[0013] The present invention also provides a method for preparing a ceramic oxygen-insulating material having a low thermal conductivity of a ceramic body after sintering, comprising the following preparation steps:
[0014] (1) weighing the raw material components and proportions of the ceramic oxygen barrier material having a low thermal conductivity of the ceramic body after sintering described above;
[0015] (2) sequentially adding the weighed raw materials of step (1) into the mixing chamber of the mixer, and then lowering the top bolt of the mixer for pressurized mixing. When the temperature of the mixing chamber rises to the first mixing temperature, the top bolt is raised to turn the materials for the first time, and after the turning of the materials is completed, the top bolt is lowered to pressurize the mixing. When the temperature of the mixing chamber rises to the second mixing temperature, the top bolt is raised to turn the materials for the second time, and after the turning of the materials is completed, the top bolt is lowered to pressurize the mixing. When the temperature of the mixing chamber rises to the third mixing temperature, the top bolt is raised to discharge the materials.
[0016] (3) The material after the internal mixing in step (2) is added into a double-stage extruder for extrusion granulation to obtain a ceramic oxygen-insulating material with a low thermal conductivity of the ceramic body after sintering.
[0017] Furthermore, the first banburying temperature is 120°C, the second banburying temperature is 150°C, and the third banburying temperature is 160°C.
[0018] Furthermore, the setting parameters of the two-stage extruder are: the temperature of zone 1 is 150°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 145°C, the temperature of zone 4 is 145°C, the temperature of zone 5 is 140°C, the temperature of zone 6 is 140°C, the temperature of zone 7 is 135°C, the temperature of zone 8 is 135°C, the temperature of zone 9 is 100°C, the temperature of zone 10 is 110°C, the temperature of zone 11 is 130°C, the temperature of zone 12 is 140°C, the screen changing temperature is 150°C, the head temperature is 155°C, the material temperature is 155°C, the pressure is ≤20MPa, and the feeding frequency is ≤30Hz.
[0019] By adopting the above technical solution, the present invention has the following beneficial effects:
[0020] (1) The ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering of the present invention adopts EPDM resin, POE resin, vinyl silicone rubber, POE compatibilizer, silicone powder, compound flame retardant, sericite powder, calcium silicate nano whisker, ceramicizing aid, silane coupling agent A-171, vulcanizing agent, and vinyl silicone oil as raw material components. The obtained ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering has good flame retardant performance, low thermal conductivity of the ceramic body after sintering, and high three-point bending strength of the ceramic body after sintering.
[0021] (2) The composite flame retardant of the ceramic oxygen-insulating material for low-sintered ceramic body of the present invention adopts MCA flame retardant. MCA flame retardant foams at high temperature, which can effectively improve the thermal conductivity of the ceramic body after sintering and the thermal insulation of the ceramic oxygen-insulating material after ceramicization.
[0022] (3) The ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering of the present invention is compounded with MCA flame retardant and diethyl aluminum hypophosphite coated phenyl silicone resin, and the obtained ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering has better flame retardancy;
[0023] (4) The ceramic oxygen-insulating material of the present invention has a low thermal conductivity after sintering. It uses phosphate-based low-temperature glass powder to coat magnesium silicate as a ceramicizing aid. After burning at high temperature, the organic materials are basically decomposed and volatilized. The phosphate-based low-temperature glass powder plays a liquid phase bridging role during the combustion process and reacts with magnesium silicate and other silicates and silicon dioxide to form a eutectic reaction to sinter into porcelain. Compared with the conventional method of directly adding low-temperature glass powder, the ceramic body after sintering has higher bending strength and is not easy to break.
[0024] (5) The ceramic insulation material of the present invention has a low thermal conductivity after sintering. The ceramic insulation material has a low thermal conductivity after sintering, which can protect the internal insulation layer.
[0025] (6) The base resin of the present invention is a composite of EPDM resin, POE resin and vinyl silicone rubber. The obtained ceramic oxygen insulation material has a low thermal conductivity of the ceramic body after sintering and has good flame retardant properties. The thermal conductivity of the sintered ceramic body is low and the three-point bending strength of the sintered ceramic body is good. DETAILED DESCRIPTION
[0026] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0027] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0028] Example
[0029] A method for preparing a ceramic oxygen barrier material with a low thermal conductivity of a ceramic body after sintering, comprising the following preparation steps:
[0030] (1) Weigh the following raw material components and proportions: 7-10 parts of EPDM resin, 11-10 parts of POE resin, 4-6 parts of vinyl silicone rubber, 6 parts of POE compatibilizer, 1 part of silicone powder, 15 parts of MCA flame retardant, 10-15 parts of diethyl aluminum hypophosphite coated phenyl silicone resin, 25 parts of sericite powder, 5 parts of calcium silicate nano whiskers, 10-12 parts of porcelainizing agent, 0.12-0.2 parts of vulcanizing agent DCP, 0.5-0.8 parts of silane coupling agent A-171, and 0.4-0.8 parts of vinyl silicone oil;
[0031] (2) adding the weighed raw materials of step (1) into the mixing chamber of the mixer in order, and then lowering the top bolt of the mixer for pressurized mixing. When the temperature of the mixing chamber rises to 120°C, the top bolt is raised to turn the materials for the first time, and after the turning of the materials is completed, the top bolt is lowered for pressurized mixing. When the temperature of the mixing chamber rises to 150°C, the top bolt is raised to turn the materials for the second time, and after the turning of the materials is completed, the top bolt is lowered for pressurized mixing. When the temperature of the mixing chamber rises to 160°C, the top bolt is raised to discharge the materials.
[0032] (3) adding the material after the banburying in step (2) into a two-stage extruder for extrusion granulation to obtain a ceramic oxygen-insulating material with a low thermal conductivity of the ceramic body after sintering; wherein the setting parameters of the two-stage extruder are: the temperature of zone 1 is 150°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 145°C, the temperature of zone 4 is 145°C, the temperature of zone 5 is 140°C, the temperature of zone 6 is 140°C, the temperature of zone 7 is 135°C, the temperature of zone 8 is 135°C, the temperature of zone 9 is 100°C, the temperature of zone 10 is 110°C, the temperature of zone 11 is 130°C, the temperature of zone 12 is 140°C, the screen changing temperature is 150°C, the head temperature is 155°C, the material temperature is 155°C, the pressure is ≤20MPa, and the feeding frequency is ≤30Hz.
[0033] The POE compatibilizer is at least one of POE-g-MAH and POE-g-GMA.
[0034] Diethyl aluminum hypophosphite coated phenyl silicone resin: TP902C Yongqi Material Technology (Shanghai) Co., Ltd.;
[0035] Phosphate-based low-temperature glass powder coated magnesium silicate: Fireproof20 Shanghai Zhuangjing Chemical Co., Ltd.,
[0036] The following Table 1 shows the raw material components and weight parts of Examples 1 to 3 and Comparative Examples 1-1, 2-1 and 3-1;
[0037] The feed amounts of each raw material component in Examples 1 to 3 are shown in the following table. The preparation method of the ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering is the same as that in the examples;
[0038] The difference between Comparative Example 1-1 and Example 1 is that Comparative Example 1-1 does not add MCA flame retardant and diethyl aluminum hypophosphite coated phenyl silicone resin, and the remaining components, feed amounts, and preparation methods are the same as those of Example 1;
[0039] The difference between Comparative Example 1-2 and Example 1 is that no MCA flame retardant is added to Comparative Example 1-1, and the remaining components, feed amounts, and preparation methods are the same as those of Example 1;
[0040] The difference between Comparative Example 1-3 and Example 1 is that no diethyl aluminum hypophosphite-coated phenyl silicone resin is added to Comparative Example 1-1, and the remaining components, feed amounts, and preparation methods are the same as those of Example 1;
[0041] The difference between Comparative Example 2-1 and Example 2 is that low-temperature glass powder is used instead of phosphate-based low-temperature glass powder to coat magnesium silicate, and the other components, feed amounts, and preparation methods are the same as those of Example 1;
[0042] The only difference between Comparative Example 3-1 and Example 3 is that the base resin is only EPDM resin and POE resin composite instead of EPDM resin, POE resin and vinyl silicone rubber composite. The other components, feed amounts and preparation methods are the same as those in Example 1.
[0043] Table 1
[0044]
[0045]
[0046]
[0047] Table 2 below shows the performance test data of the ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering of Examples 1 to 3 and Comparative Examples 1-1, 2-1 and 3-1:
[0048] Table 2
[0049]
[0050]
[0051] Referring to Tables 1-2, it can be seen that, compared with Comparative Examples 1-1, Comparative Example 2-1, and Comparative Example 3-1, the flame retardant properties of the ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering prepared by the present invention are better, the thermal conductivity of the sintered ceramic body is lower, and the three-point bending strength of the sintered ceramic body is better; compared with Example 1, Comparative Example 1-1 adds MCA flame retardant, diethyl aluminum hypophosphite coated phenyl silicone resin, and the flame retardant properties of the ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering are better, and the thermal conductivity of the sintered ceramic body is higher. The thermal coefficient is lower; compared with Example 1, the ceramic body after sintering of the ceramic body with low thermal conductivity prepared by coating magnesium silicate with phosphate-based low-temperature glass powder has better three-point bending strength; compared with Example 1, the ceramic body after sintering of the ceramic body with low thermal conductivity prepared by composite of EPDM resin, POE resin and vinyl silicone rubber as the base resin has better flame retardant properties, lower thermal conductivity of the ceramic body after sintering, and better three-point bending strength of the ceramic body after sintering.
[0052] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering, characterized in that: In terms of weight, the raw material components include: 7-10 parts of EPDM resin, 11-10 parts of POE resin, 4-6 parts of vinyl silicone rubber, 6 parts of POE compatibilizer, 1 part of silicone powder, 25-30 parts of compound flame retardant, 25 parts of sericite powder, 5 parts of calcium silicate nano whiskers, 10-12 parts of porcelain additive, 0.5-0.8 parts of silane coupling agent A-171, 0.12-0.2 parts of vulcanizer, and 0.4-0.8 parts of vinyl silicone oil.
2. The ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering according to claim 1, characterized in that: The POE compatibilizer is at least one of POE-g-MAH and POE-g-GMA.
3. The ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering according to claim 1, characterized in that: The compound flame retardant includes MCA flame retardant.
4. The ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering according to claim 3, characterized in that: The compound flame retardant further comprises diethyl aluminum hypophosphite coated phenyl silicone resin.
5. The ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering according to claim 1, characterized in that: The porcelainizing auxiliary agent is a phosphate-based low-temperature glass powder coated with magnesium silicate.
6. The ceramic oxygen barrier material with low thermal conductivity of ceramic body after sintering according to claim 1, characterized in that: The vulcanizing agent includes dicumyl peroxide.
7. A method for preparing a ceramic oxygen barrier material having a low thermal conductivity of a ceramic body after sintering, characterized in that: The method comprises the following preparation steps: (1) Weighing the raw material components and proportions of the ceramic oxygen barrier material with low thermal conductivity of the ceramic body after sintering according to any one of claims 1 to 6; (2) sequentially adding the weighed raw materials of step (1) into the mixing chamber of the mixer, and then lowering the top bolt of the mixer for pressurized mixing. When the temperature of the mixing chamber rises to the first mixing temperature, the top bolt is raised to turn the materials for the first time, and after the turning of the materials is completed, the top bolt is lowered to pressurize the mixing. When the temperature of the mixing chamber rises to the second mixing temperature, the top bolt is raised to turn the materials for the second time, and after the turning of the materials is completed, the top bolt is lowered to pressurize the mixing. When the temperature of the mixing chamber rises to the third mixing temperature, the top bolt is raised to discharge the materials. (3) The material after the internal mixing in step (2) is added into a double-stage extruder for extrusion granulation to obtain a ceramic oxygen-insulating material with a low thermal conductivity of the ceramic body after sintering.
8. The method for preparing a ceramic oxygen barrier material having a low thermal conductivity of a ceramic body after sintering according to claim 7, characterized in that: The first banburying temperature is 120°C, the second banburying temperature is 150°C, and the third banburying temperature is 160°C.
9. The method for preparing a ceramic oxygen barrier material having a low thermal conductivity of a ceramic body after sintering according to claim 7, characterized in that: The setting parameters of the two-stage extruder are: the temperature of zone 1 is 150°C, the temperature of zone 2 is 150°C, the temperature of zone 3 is 145°C, the temperature of zone 4 is 145°C, the temperature of zone 5 is 140°C, the temperature of zone 6 is 140°C, the temperature of zone 7 is 135°C, the temperature of zone 8 is 135°C, the temperature of zone 9 is 100°C, the temperature of zone 10 is 110°C, the temperature of zone 11 is 130°C, the temperature of zone 12 is 140°C, the screen changing temperature is 150°C, the head temperature is 155°C, the material temperature is 155°C, the pressure is ≤20MPa, and the feeding frequency is ≤30Hz.
